The Power of Patients Attitude towards Repurchase Intention of Hospital Services in Sumedang - Nesya Noer Kemalasari; Endang Ruswanti; Kemala Rita Wahidi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Introduction: Repurchase intention is one of the important indicators in the world of health services, especially in hospitals. XYZ General Hospital must evaluate the services provided to patients by understanding patient perceptions, particularly through patient experience, as 50% of respondents expressed unwillingness to recommend or reuse the hospital’s services. This highlights a potential gap between service delivery and patient expectations. Method The purpose of this study was to analyze the influence of patient experience, brand image, and trust on repurchase intention at XYZ Hospital, with attitude as an intervening variable. This study employed a quantitative explanatory research design, involving 182 patients from outpatient and inpatient units who had visited more than once. Data were collected through structured questionnaires and analyzed using the Structural Equation Model (SEM) with the Partial Least Square (PLS) method, supported by the SmartPLS software. Results: The results revealed that patient experience, brand image, and trust significantly affect patient attitudes, which in turn directly influence repurchase intention. Attitude serves as a mediating variable between patient experiences, brand image, trust, and repurchase intention. Simultaneous testing confirmed that all independent variables have a joint effect on repurchase intention. Among the variables tested, attitude showed the strongest direct influence on repurchase intention, while patient experience had the highest indirect effect through attitude. Conclusion: These findings underscore the critical role of patient experience in shaping positive perceptions of service quality, which contribute to strengthening brand image, increasing trust, and fostering patient attitudes that support future service utilization. Therefore, healthcare providers must prioritize improving communication, staff responsiveness, and patient-centered care to enhance overall experience, build loyalty, and ensure long-term sustainability of healthcare services.